Estudo comparativo entre os resultados de testes para diagnóstico da infecção do vírus da imunodeficiência humana em amostras de soro e de saliva - Cardoso, Silvia (Brazilian Journal of Sexually Transmitted Diseases, 1995)
The objetive of the study to compare the results of diagnost1c tests for HJV infection in serum and saliva samples. We studied 20 patients infected with HIV, 20 healthy persons and 12 persons with other infectious infectious and auto-immune persons .. We collected serum and saliva samples of ali, the serum simples were obtained using venous punction and salira specimens were obtained using the "omnisal" (Saliva Diagnostics Systems, Inc.). The samples (serum and saliva) were assayed by the following tests: HIV-1 RECOJ\1BINANT (Abbott), HIV-1/HIV-2 recombinant (Abbott), LAV-EIA (Genetic Systems) and the indirect aglutination using the Serodia - HJV (Fujirebio, Inc.) Ali the positive samples (serum and saliva) were confirmed by Western Blot assay (Organon Tekinika). The authors conclued that results showed a good correlation between the di:fferent kind of samples studied (serum and saliva) and detectingHIV antibodies in salivasamples is agood altemative method.